2019
DOI: 10.1103/physreve.99.063317
|View full text |Cite
|
Sign up to set email alerts
|

Simulating the nonlinear interaction of relativistic electrons and tokamak plasma instabilities: Implementation and validation of a fluid model

Abstract: For the simulation of disruptions in tokamak fusion plasmas, a fluid model describing the evolution of relativistic runaway electrons and their interaction with the background plasma is presented. The overall aim of the model is to self-consistently describe the non-linear coupled evolution of runaway electrons (REs) and plasma instabilities during disruptions. In this model, the runaway electrons are considered as a separate fluid species in which the initial seed is generated through the Dreicer source, that… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
37
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 40 publications
(37 citation statements)
references
References 34 publications
0
37
0
Order By: Relevance
“…Using the free boundary JOREK-STARWALL code [32], also vertical stability and control will be taken into account and runaway electron dynamics will be studied using the models described in Refs. [13,14]. Numerical improvements which are presently ongoing, are expected to reduce the computational costs and enhance numerical stability at fully realistic parameters.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Using the free boundary JOREK-STARWALL code [32], also vertical stability and control will be taken into account and runaway electron dynamics will be studied using the models described in Refs. [13,14]. Numerical improvements which are presently ongoing, are expected to reduce the computational costs and enhance numerical stability at fully realistic parameters.…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies for massive gas and shattered pellet injection [7][8][9][10][11][12] demonstrate some of the capabilities. The code allows also to study the dynamics of runaway electrons [13,14] and vertical displacement events [15,16] which are closely related to (mitigated) disruptions. In the present article, only a small subset of the code features is invoked to perform first predictive simulations for deuterium SPI into an ASDEX Upgrade H-mode plasma.…”
Section: Introductionmentioning
confidence: 99%
“…In this scenario, we observed that the plateau runaway current was significantly reduced when using the neural network instead of the Connor-Hastie formula, which demonstrates the need to account for partially ionized atoms for realistic modelling of Dreicer generation. The neural network presented here can therefore be useful to improve runaway-electron modelling in tokamak simulation codes such as astra (Fable et al 2016), jorek (Bandaru et al 2019), and ets (Pokol et al 2019…”
Section: Discussionmentioning
confidence: 99%
“…Magnetized relativistic environments are known to exist in different situations like in active galactic nuclei (jets produced by the rotation of heavy black holes) (Petropoulou et al 2019), other astrophysical objects (such as neutron stars, pulsars, micro-quasars, etc.) (Beskin et al 1988;Chabrier et al 2002;Melrose 2017) and Van Allen radiation belts (Horne et al 2005), and also have primary importance in tokamak plasmas (Bandaru et al 2019) and laser-plasma interactions (Banerjee et al 2002).…”
Section: Introductionmentioning
confidence: 99%